Problems Faced by Women Entrepreneurs in Thoothukudi District - et.al, D. Shakila (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Women entrepreneurship is the process of setting up an enterprise, picking on any risks in the faith of profit. Women are these days winning in each and every field identical to men. Women entrepreneurs play a massive role in this male dominated society. Women are abutting lots of changes and problems prevailing in this society. Empowering women in entrepreneurship commands to break the inequalities and decreases scarcity. Basically entrepreneurs come across with many hardships that limit their prosperity and longevity. Besides this, women are working very excellently but they have many barriers in initiating and running their own business because of family problem, problems of finance, scarcity of Raw Materials, marketing constraints, numerous standards and customs etc. This paper helps to understand the countless problems faced by women entrepreneurs in the study area and suggests several measures to overcome those problems